Roman religion - Warrior, Valerie M. (Cambridge ; New York : Cambridge University Press, 2006)
"This book provides an introduction to the religion and religious practices of ancient Rome. Examining sites that are familiar to many modern tourists, Valerie Warrior avoids imposing a modern perspective on the topic by using the testimony of the ancient Romans to describe traditional Roman religion. The ancient testimony re-creates the social and historical contexts in which Roman religion was practiced. Carefully integrated with the text are visual representations of divination, prayer, and sacrifice as depicted on monuments, coins, and inscriptions from public buildings and homes throughout the Roman world. Also included are epitaphs and humble votive offerings that illustrate the piety of individuals and that reveal the prevalence of magic and the occult in the lives of the ancient Romans."--BOOK JACKET.
The gods and their worship -- Divination, prayer, and sacrifice -- Religion and the family -- Religion and the state -- Religion and war -- The calendar, festivals, and games -- Official attitudes toward foreign cults -- Magic and the occult -- Becoming a god -- The Jews and Christianity.
Includes bibliographical references (p. 149-155) and index.
Keywords: Rome (Italy) -- Religion; Religion romaine